2013
DOI: 10.3109/15622975.2013.819120
|View full text |Cite
|
Sign up to set email alerts
|

1H-MRS of hippocampus in patients after first manic episode

Abstract: Our results suggest that early in the course of BD there are no alterations in neuronal metabolism or vulnerability in the hippocampus after the first manic episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
3
6
0
Order By: Relevance
“…Conflicting results in previous studies may be due to heterogeneous technical approaches for spectra quantification, poor study design, and enrollment of medicated patients at different phases of the illness ( Capizzano et al, 2007 ; Kraguljac et al, 2012 ). Our results are in line with the largest 1H-MRS investigation conducted to date in BD ( Gigante et al, 2014 ), which found no differences with regard to NAA, Cr, mI, Cho, and Glx levels in BD type I patients (medicated and at variable mood states on the day of 1H-MRS scanning) compared to healthy controls.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Conflicting results in previous studies may be due to heterogeneous technical approaches for spectra quantification, poor study design, and enrollment of medicated patients at different phases of the illness ( Capizzano et al, 2007 ; Kraguljac et al, 2012 ). Our results are in line with the largest 1H-MRS investigation conducted to date in BD ( Gigante et al, 2014 ), which found no differences with regard to NAA, Cr, mI, Cho, and Glx levels in BD type I patients (medicated and at variable mood states on the day of 1H-MRS scanning) compared to healthy controls.…”
Section: Discussionsupporting
confidence: 91%
“…Also, only three studies have assessed Glu or Glx levels in the hippocampus of subjects with BD. Senaratne et al (2009) and Gigante et al (2014) did not find differences in Glx levels between BD patients and healthy controls. Colla et al (2009) only found elevated Glu concentrations in euthymic BD subjects under lithium treatment compared to healthy controls.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103, 104, 105, 106 The most consistent finding was reduced NAA, which was detected in 7/15 studies. 91, 92, 93, 94, 97, 100, 103 One study reported increased NAA, 102 and the remainder found no diagnosis-related differences.…”
Section: Discussionmentioning
confidence: 82%
“…However, some studies did not show a decrease in NAA levels [137139]. Differences in findings may correspond to different brain regions analyzed [137] or disease characteristics of the sample population such as short length of illness [140]. Several studies have shown negative correlations between NAA and illness duration [129,132,141] suggesting that reductions in NAA levels may become more pronounced with the progression of BPD.…”
Section: Mitochondrial Dysfunction In Bpdmentioning
confidence: 99%